Functional, Structural and Contextual Analysis of a Variant of Uncertain Clinical Significance in BRCA1: c.5434C->G (p. Pro1812Ala) - Morales, Rafael; Serrano, Raquel; Sardón, Teresa; Román-Ortíz, Carmen; González-Santiago, Santiago; Mulet, Roger; Manuel Mas, José (Journal of Cancer Genetics And Biomarkers, 2017)
Interpreting variants of uncertain significance (VUS) for their effect on protein function, and therefore for the risk of developing cancer, has become a challenge in clinical practice for genetic counselling services. The present work combines structural bioinformatics and systems biology based mathematical modelling approaches with the aim of determining the pathogenicity of the mutation c.5434C->G (p.Pro1812Ala) in the BRCA1 gene (detected in a patient from a high risk family) and also to mechanistically understand the effect of this mutation in DNA damage response, a key process in cancer development. The results obtained showed that this mutation prevents the interaction of BRCA1 with key proteins of the cell cycle, subsequently impairing BRCA1-dependent induction of cell cycle arrest. The comparison of the molecular mechanisms associated with the native BRCA1 protein and the mutated variant function in DNA damage response showed that the latter undergoes a reduction in its ability to modulate pathways that are critical for DNA repair and cell cycle control. Therefore, this variant will not be able to exert its tumor suppressive action. Interestingly, these conclusions can be extrapolated to all mutations that, like c.5434C>G (p.Pro1812Ala) BRCA1, cause loss of BRCT domain activity.
Keywords: Hereditary Breast and Ovarian Cancer; BRCA1 gen; Variant of Uncertain Clinical; Systems Biology